Model Asuhan Keluarga Kristen di Masa Pandemi Covid-19 - Albet Saragih; Johanes Waldes Hasugian (JURNAL TERUNA BHAKTI, 2020)
This paper is the result of an analysis of the practical situation of family education in the Christian community in the midst of a global pandemic. When the government has to limit its citizens to stay at home, stay at home, work from home, social distancing, wear masks, wash their hands; then all of this has an impact on difficulties for families. Children learn distance (online) from home. It is the parents who play a bigger role in learning, the burden on teachers and schools is increasingly formalized. Christian parents face formidable challenges in realizing their vocation and role in today's situation. Based on the research conducted, various efforts should be made by Christian parents in terms of Christian parenting during the Covid-19 pandemic, including Restoration of initial love, which is rooted in the love relationship between husband and wife that has been blessed by God and restoration of love with God, restoration of an initial love for children, proven patience, preparation of good nutrition for all family members, and continuing to share love, as a model of exemplary care for children. This paper was written using a descriptive method, namely through the use of literature or literature sources, especially with regard to the parenting style of Christian’s parents during the pandemic. Abstrak: Tulisan ini adalah hasil analisis terhadap situasi praktis pendidikan keluarga komunitas kristiani di tengah pandemi melanda dunia. Ketika pemerintah harus membatasi warganya untuk tinggal di rumah saja, stay at home, work from home, social distancing, harus pakai masker, cuci tangan; maka semua ini berdampak kesulitan bagi para keluarga. Anak-anak belajar jarak jauh (online) dari rumah. Orang tualah yang lebih banyak berperan dalam pembelajaran, beban guru dan sekolah semakin terporalisasi. Para orang tua Kristen menghadapi tantangan berat dalam mewujudkan panggilan dan perannya dalam situasi seperti sekarang ini. Berdasarkan penelitian yang dilakukan maka ditemukanlah berbagai upaya yang hendaknya dilakukan oleh orang tua Kristen dalam hal pengasuhan yang kristiani di saat pandemi covid-19, antara lain: Pemulihan kasih mula-mula, yang berakar pada dasar hubungan kasih suami-istri yang sudah diberkati Tuhan dan pemulihan kasih dengan Tuhan, Pemulihan kasih mula-mula terhadap anak, Kesabaran yang teruji, Penyiapan gizi yang baik buat semua anggota keluarga, dan tetap berbagi kasih, sebagai model asuhan keteladanan bagi anak-anak. Tulisan ini dibuat dengan menggunakan metode deskriptif, yaitu melalui pemanfaatan sumber literatur atau pustaka, khususnya berkenaan dengan pola asuh orang tua Kristsen di masa pandemi.